Geomechanical rock properties of a basaltic volcano - Schaefer, Lauren N.; Kendrick, Jackie E.; Oommen, Thomas; Lavallée, Yan; Chigna, Gustavo (Frontiers in Earth Science, 2015)
In volcanic regions, reliable estimates of mechanical properties for specific volcanic events such as cyclic inflation-deflation cycles by magmatic intrusions, thermal stressing, and high temperatures are crucial for building accurate models of volcanic phenomena. This study focuses on the challenge of characterizing volcanic materials for the numerical analyses of such events. To do this, we evaluated the physical (porosity, permeability) and mechanical (strength) properties of basaltic rocks at Pacaya Volcano (Guatemala) through a variety of laboratory experiments, including: room temperature, high temperature (935 °C), and cyclically-loaded uniaxial compressive strength tests on as-collected and thermally-treated rock samples. Knowledge of the material response to such varied stressing conditions is necessary to analyze potential hazards at Pacaya, whose persistent activity has led to 13 evacuations of towns near the volcano since 1987. The rocks show a non-linear relationship between permeability and porosity, which relates to the importance of the crack network connecting the vesicles in these rocks. Here we show that strength not only decreases with porosity and permeability, but also with prolonged stressing (i.e., at lower strain rates) and upon cooling. Complimentary tests in which cyclic episodes of thermal or load stressing showed no systematic weakening of the material on the scale of our experiments. Most importantly, we show the extremely heterogeneous nature of volcanic edifices that arise from differences in porosity and permeability of the local lithologies, the limited lateral extent of lava flows, and the scars of previous collapse events. Input of these process-specific rock behaviors into slope stability and deformation models can change the resultant hazard analysis. We anticipate that an increased parameterization of rock properties will improve mitigation power.